Wonderstruck [videorecording (DVD)] - Fegley, Oakes; Moore, Julianne; Michael, Jaden (Actor); Selznick, Brian (Lionsgate, 2018)
Tells the tale of two deaf children separated by fifty years. In 1927 New York City, Rose searches for the actress who's life she chronicles in her scrapbook; in 1977 in the Midwest, Ben runs away from home to find his father. The movie is based on the novel of the same title by Brian Selznick, which is the predecessor to his screen-adapted novel The Invention of Hugo Cabret.